Magnetic Resonance Imaging (MRI) Appearances of Primary Amelanotic Malign Melanoma in the Nasal Cavity: A Rare Case - Günbey, Hediye Pınar; Günbey, E.; Tanrivermiş Sayit, A.T.; Aslan, K. (Journal of Clinical and Diagnostic Research editor-in-chief@jcdr.net No 3, 1/9 Roop Nagar, G T Road, Delhi 110007, 2015)
Malign melanoma of the nasal cavity that arises at such an unusual location is an exceptional case only occasionally mentioned in the literature. An amelanotic form, which is an uncommon type for this malignancy, also has an unusual radiological appearence from the classic melanotic form. We report here the magnetic resonance imaging (MRI) findings of a 46-year-old man who had a nasal cavity mass diagnosed as an amelanotic malign melanoma and discuss the importance of differential diagnosis with such an unusual radiological manifestation in this location. © 2015, Journal of Clinical and Diagnostic Research. All rights reserved.
Keywords: Amelanotic Malign Melanoma; MRI; Nasal Cavity